Evolution of durum wheat from Sicilian landraces to improved varieties - Sciacca F.; Cambrea M.; Licciardello S.; Pesce A.; Romano E.; Spina A.; Virzì N.; Palumbo M. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
In the early twentieth century a large number of durum wheat landraces were grown in Sicily. They were characterized by high adaptability to Mediterranean environments and were composed of a mixture of different genotypes. In recent decades the genetic improvement has led to the constitution of modern durum wheat cultivars made up of individual pure lines, highly uniform and productive. Today, the old tetraploid landraces are a precious source of biodiversity and can be successfully used in breeding programs aimed to improving technological quality and resistance to biotic and abiotic stresses. Some of these landraces are still cultivated and used for the production of typical local breads. In the present work twelve Sicilian old landraces have been compared with sixteen durum wheat improved cultivars. For all genotypes morphological parameters were detected according to UPOV and IPGRI descriptors; biochemical characterization was performed by SDS – PAGE of low molecular weight and high molecular weight gluten subunits; molecular analyses were carried out using SSR with thirteen primer pairs. The joint analysis of the results allowed an assessment of genetic diversity between the two groups of genotypes.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)